Optimization of process parameters in preparation of tocotrienol-rich red palm oil-based nanoemulsion stabilized by Tween80-Span 80 using response surface methodology - Chong, Wai Ting; Tan, Chin Ping; Cheah, Yoke Kqueen; Lajis, Ahmad Firdaus; Mat Dian, Noor Lida Habi; Kanagaratnam, Sivaruby; Lai, Oi Ming (Public Library of Science, 2018)
Red palm oil (RPO) is a natural source of Vitamin E (70–80% tocotrienol). It is a potent natural antioxidant that can be used in skin-care products. Its antioxidant property protects skin from inflammation and aging. In our work, a tocotrienol-rich RPO-based nanoemulsion formulation was optimized using response surface methodology (RSM) and formulated using high pressure homogenizer. Effect of the concentration of three independent variables [surfactant (5–15 wt%), co-solvent (10–30 wt%) and homogenization pressure (500–700 bar)] toward two response variables (droplet size, polydispersity index) was studied using central composite design (CCD) coupled to RSM. RSM analysis showed that the experimental data could be fitted into a second-order polynomial model and the coefficients of multiple determination (R2) is 0.9115. The optimized formulation of RPO-based nanoemulsion consisted of 6.09 wt% mixed surfactant [Tween 80/Span 80 (63:37, wt)], 20 wt% glycerol as a co-solvent via homogenization pressure (500 bar). The optimized tocotrienol-rich RPO-based nanoemulsion response values for droplet size and polydispersity index were 119.49nm and 0.286, respectively. The actual values of the formulated nanoemulsion were in good agreement with the predicted values obtained from RSM, thus the optimized compositions have the potential to be used as a nanoemulsion for cosmetic formulations.